TOWARDS IMPLEMENTATION AND ACHIEVEMENT OF CONSTRUCTION AND ENVIRONMENTAL QUALITY IN THE MALAYSIAN CONSTRUCTION INDUSTRY (Malaysian Journal of Civil Engineering, 2018)
The purpose of this paper is to identify mechanisms and approaches involved in the local construction individuals and companies to enhance environmental concerns and the adoption of interdisciplinary method of managing the environment and up keeping of the quality in Malaysian Construction Industry. This paper describes an innovative approach to understanding the role of internal and external influence through LEGO concept. This approach builds on theories of environmental issues, in which learning about new ideas, practices or technologies occurs through integration of efforts particularly from the government. The approach also analyses the challenges faced by construction stakeholders. It draws on findings from different studies including some other countries of sustainability in which the engagement of previous research has been incorporated to speed up the environmental sustainability in Malaysia. Environmental sustainable development construction requires a holistic thinking and decision making and more innovative solutions that enhance sustainability and result in mutually benefited outcomes for all stakeholders. A dedicated effort especially government and government link company is in strong demand. This integrated achievement boosts the awareness and action among stakeholders. The role of government and leaders has been cited as an important component towards of environmental sustainability. Development of the approach will contribute to the understanding of environmental sustainability through identifying gaps in the understanding and pursuit of sustainability in the Malaysian construction industry. This paper suggests the future prospect that integrates several dimensions towards sustainability practice in Malaysia.